Antioxidant Small Molecule Compound Chrysin Promotes the Self-Renewal of Hematopoietic Stem Cells - Li, Yinghui; He, Mei; Zhang, Wenshan; Yang, Ming; Ding, Yahui; Xu, Shiqi; Gu, Jiali; Li, Yafang; Yin, Jingjing; Gao, Yingdai (Frontiers in Pharmacology, 2020)
There is an increasing demand for the expansion of functional human haematopoietic stem cells (hHSCs) for various clinical applications. Based on our primary screening of antioxidant small molecule compounds library, a small molecule compound C2968 (chrysin) was identificated to expand cord blood CD34+ cells in vitro. Then we further verified the optimum concentration and explored its effect on hHSCs phenotype and biological function. C2968 could significantly increase the proportion and absolute number of CD34+CD38-CD49f+ and CD34+CD38-CD45RA-CD90+ cells under 2.5μM. Furthermore, the total number of colony-forming units and the frequency of LT-HSCs in C2968-treated group were significantly higher than control, indicating the multipotency and long-term activity of hematopoietic stem and progenitor cells were sustained. Additionally, C2968 treatment could maintain transplantable HSCs that preserve balanced multilineage potential and promote rapid engraftment after transplantation in immunodeficient (NOG) mice. Mechanistically, the activity of chrysin might be mediated through multiple mechanisms namely delaying HSC differentiation, inhibiting ROS-activated apoptosis, and modulating of cyclin-dependent kinase inhibitors. Overall, chrysin showed good ex vivo expansion effect on hHSCs, which could maintain the self-renewal and multi-lineage differentiation potential of hHSCs. Through further research on its antioxidant mechanism, it may become a promising tool for further fundamental research and clinical umbilical cord blood transplantation of hHSCs.